Women, Gender, and Sexuality in China : A Brief History. - Yao, Ping (Professor of history) ([Place of publication not identified] : Routledge, 2021)
Women, Gender and Sexuality in China serves as a focal textbook for undergraduate courses on women, gender, and sexuality in Chinese history. Thematically structured, it surveys important aspects of gender systems and gender practices throughout Chinese history, from the earliest period to the modern era. Topics include the concept of yin-yang, life course and gender roles, kinship systems and family structure, marriage practices, sexuality, womenś work and daily life, as well as gender in Chinese mythology, religions, medicine, art, and literature. In narrating how various traditions and practices were formed and evolved throughout Chinese history, this textbook draws heavily on personal stories and historical records. Features in this textbook include: Primary source sections for each chapter, introducing students to types of documents that have been used by scholars in conducting research 33 translated texts of various genres, including epitaph, bronze inscription, medical text, imperial edict, legal case, family letter, ghost story, divorce paper, poetry, autobiography, etc Dedicated biography sections for five distinguished women Offering richly layered accounts of women, gender, and sexuality, this textbook is essential reading for students of Chinese history, gender in world history, or the comparative history of gender.
1. Life Courses and Gender Roles 2. Marriage and Family 3. Sex, Body, and Medicine 4. Labor, Profession, and Everyday Life 5. Religions 6. Arts, Literature, and Education 7. Five Women to Remember
Keywords: HISTORY / Asia / China; Sex -- China -- History; Sex role -- China -- History; Women -- China -- History